Surgically resected T1‐ and T2‐stage esophageal squamous cell carcinoma: T and N staging performance of EUS and PET/CT - Jeong, Dong Young (John Wiley and Sons Inc., 2018)

(untitled) (Cancer Med)
This study aimed to evaluate the frequency of nodal metastases and to disclose the diagnostic performance of endoscopic ultrasonography (EUS) and PET/CT in T and N staging in surgically resected early‐stage esophageal squamous cell carcinomas (eSCCs). Institutional review board approved this retrospective study with waiver of informed consent for reviewing medical record. We included 435 patients with an early T‐stage (Tis or T1a [≤T1a], T1b and T2) eSCC. The rates of metastatic lymphadenopathy were calculated. Then, the performance of EUS and PET/CT in subdividing T and N stages was assessed. 131 ≤ T1a, 234 T1b, and 70 T2 eSCCs were identified. In discriminating ≤T1a from other cancers, the sensitivity, specificity, and accuracy of EUS were 60.3% (79/131), 80.3% (244/304), and 74.3% (323/435) respectively. With ROC curve analysis, cut‐off value of SUVmax 3.05 at PET provided sensitivity 74.8% (98/131), specificity 70.1% (213/304), and accuracy 71.5% (311/435) for differentiating ≤T1a eSCCs from others. Ten (7.6%) of 131 ≤ T1a cancers had nodal metastasis. In discriminating N0 from node‐positive disease, sensitivity, specificity, and accuracy of EUS were 89.6% (267/298), 41.6% (57/137), and 74.5% (324/435), respectively, whereas those of PET/CT were 88.9% (265/298), 38.7% (53/137), and 73.1% (318/435) respectively. In >70% of patients with ≤T1a eSCCs, the tumor stage can be discriminated from higher stage cancers by using EUS or PET/CT. Substantial percentage (7.6%) of ≤T1a eSCC patients have nodal metastases, which are missed in more than half of the patients in clinical staging.